Utilizing electronic resources to promote your residency program - Colton Mabis; Momal Tara Chand; Shelby Miller (University of São Paulo, 2021)
As the COVID-19 pandemic spread to the United States, it was followed by unprecedented changes. These changes did not spare undergraduate and graduate medical students. Specifically, medical students applying for residency programs were faced with a novel challenge. In March 2020, as the pandemic became increasingly severe, the Association of American Medical Colleges (AAMC) recommended pulling medical students from in-person clinical rotations. By May 2020, the AAMC recommended that all residency interviews be conducted online for the 2020-2021 residency application cycle. These unprecedented modifications to the interview season required programs to quickly adapt and find ways to utilize online tools to convey what their program offered to applicants. In this paper, we will outline the adaptations, tools, and resources that residencies and applicants have used to navigate through the 2020/2021 interview cycle.